2011
DOI: 10.1108/14601061111174934
|View full text |Cite
|
Sign up to set email alerts
|

The impact of outside‐in open innovation on innovation performance

Abstract: PurposeThe purpose of this paper is to examine the influence of an open outside‐in innovation management strategy on companies' innovativeness and innovation performance. Specifically, it focuses on the adoption of the open innovation paradigm in practice and the extent of collaboration with different stakeholders.Design/methodology/approachThe proposed hypotheses are tested empirically using survey data collected from stock‐listed companies in Germany, Switzerland and Austria. The data include the complete re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(137 citation statements)
references
References 82 publications
2
115
0
9
Order By: Relevance
“…At the same time, every firm needs to pay attention and maintain good relationships with partners to enhance its own competitive ability. The partners within the supply chain are one of the most important sources of knowledge applied to develop innovative processes and the combination of the company know-how with these of suppliers, customers and external actors can increase the firm's innovativeness (Inauen, Schenker-Wicki 2011).…”
Section: Open Innovation and Outside-in Managementmentioning
confidence: 99%
“…At the same time, every firm needs to pay attention and maintain good relationships with partners to enhance its own competitive ability. The partners within the supply chain are one of the most important sources of knowledge applied to develop innovative processes and the combination of the company know-how with these of suppliers, customers and external actors can increase the firm's innovativeness (Inauen, Schenker-Wicki 2011).…”
Section: Open Innovation and Outside-in Managementmentioning
confidence: 99%
“…Customer involvement was in prior research shown to positively relate to a firm's innovation performance (Inauen and Schenker-Wicki 2011). This positive association emerged from customers' expressing their needs, which can be a great source of innovative ideas for new products and services and for continuously improving existing ones (Chesbrough 2003).…”
Section: Customer Involvementmentioning
confidence: 99%
“…For example, Laursen and Salter's (2006) findings based on the uk innovation survey suggested a curvilinear relationship between external search breadth and external search depth and innovation performance. In another study on a sample of 141 companies from three countries, Inauen and Schenker-Wicki (2011) showed that openness of the outside-in process positively relates to a firm's innovation performance; in particular, collaboration with customers and universities positively relates to product innovations, while openness towards suppliers, competitors, and universities is linked to process innovations. However, only a few studies have considered the multidimensionality of a firm's open innovation process.…”
Section: Open Innovation and A Firm's Innovation Performancementioning
confidence: 99%
“…This approach facilitates the gain and exploitation of innovative opportunities available to them, which positively relates to the firm's innovation performance (Laursen and Salter 2006). The overall positive effect of external networks on innovation has been also shown by Inauen and Schenker-Wicki (2011). Among resources in the networks, creativity, fresh ideas on product innovation, and know-how to implement such innovations (Schroll and Mild 2011) significantly contribute to market push innovations (Nijhof, Krabbendam, and Looise 2002).…”
Section: Outsourcing Randd and External Networkingmentioning
confidence: 99%
“…For example, Laursen and Salter's (2006) findings based on the uk innovation survey suggested a curvilinear relationship between external search breadth and external search depth and innovation performance. In another study on a sample of 141 companies from three countries, Inauen and Schenker-Wicki (2011) showed that openness of the outside-in process positively relates to a firm's innovation performance; in particular, collaboration with customers and universities positively relates to product innovations, while openness towards suppliers, competitors, and universities is linked to process innovations. Existing research provides overall support for the argument that there is a relationship between inbound and outbound open innovation activities and innovation performance (Chesbrough and Crowther 2006;Chesbrough 2003).…”
Section: Open Innovation and A Firm's Innovation Performancementioning
confidence: 99%